2014
DOI: 10.3390/rs6032154
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Classification of Temperate Marine Macroalgal Communities Using Bathymetric LiDAR

Abstract: Abstract:Here, we evaluated the potential of using bathymetric Light Detection and Ranging (LiDAR) to characterise shallow water (<30 m) benthic habitats of high energy subtidal coastal environments. Habitat classification, quantifying benthic substrata and macroalgal communities, was achieved in this study with the application of LiDAR and underwater video groundtruth data using automated classification techniques. Bathymetry and reflectance datasets were used to produce secondary terrain derivative surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 58 publications
1
40
0
1
Order By: Relevance
“…The methodology is useful for mapping large coastal areas to detect the structure and variation in the benthic environment. However, even if interpreted as a classification attempt, the results are comparable to those presented, for example, in [2].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The methodology is useful for mapping large coastal areas to detect the structure and variation in the benthic environment. However, even if interpreted as a classification attempt, the results are comparable to those presented, for example, in [2].…”
Section: Discussionsupporting
confidence: 66%
“…They found that combined with multispectral (three visible bands plus NIR) data, the LiDAR-derived DEM gave good classification accuracy when used for discrimination between 22 supralittoral, intertidal and subtidal habitats. Zavalas et al [2] used six features derived from the DEM (obtained using bathymetric LiDAR) combined with three reflectance-based features to produce substrata, biological and canopy habitat maps of a coastal area between Warrnambool and Port Fairy, Western Victoria, Australia. The overall classification accuracy was 75% for substrata, 72% for biological and 72% for the canopy habitat map.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current geomorphometric applications on bathymetric lidar data are mainly related to the exploration of coastal ecosystems (e.g. Wedding et al, 2008;Zavalas et al, 2014) and geomorphology (e.g. Arifin and Kennedy, 2011;Kennedy et al, 2014), but are likely to extend to other applications such as marine archaeology and natural hazards assessment (e.g.…”
Section: Bathymetric Lidarmentioning
confidence: 99%
“…In a hydrographic survey, researchers are able to measure water depth, coast line, and seabed topography using airborne bathymetric Lidar (Seo and Kim, 2008;Zavalas et al, 2014).…”
Section: Investigation Of Seabed Materials Has High Importancementioning
confidence: 99%